(untitled) (Heritage, 2025)
Sexual harassment at work is a globally widespread phenomenon, with serious detrimental effects. In addition to the directly victimized individuals, other persons engaged in a work environment characterized by the absence of healthy communication and mutual respect also suffer harmful effects, while the consequences are also felt by the wider community in which such behaviors are tolerated. Therefore, the subject of the paper is sexual harassment in the workplace, with a special focus on normative solutions and the state of practice in Serbia. The authors sought to point out the inconsistencies that characterize this area through the analysis of positive legal solutions, as well as to draw attention to the lack of research on the prevalence, dynamics and structure of sexual harassment in the workplace in Serbia. Therefore, they used content analysis and the normative-logical method. Authors conclude that doubts should be resolved regarding whether sexual harassment in the workplace must necessarily be characterized by discriminatory motivation on the part of the perpetrator, as well as the unevenness of solutions in the criminal and civil spheres. They particularly point out the need for continuous efforts to raise awareness about the characteristics and consequences of sexual harassment.